2003
DOI: 10.1590/s0101-81082003000300002
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of treatment services and systems for substance use disorders

Abstract: Scientific research and program evaluation have not played a major role in shaping the development of treatment services and systems in most countries. This has led to disparities in the development, management and monitoring of national treatment systems. In the evaluation of treatment for substance use disorders, the evaluation practitioner will usually be working at one of five levels: single case, treatment activity, treatment service, treatment agency or treatment system. One of the major barriers to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
(42 reference statements)
0
5
0
2
Order By: Relevance
“…To give a second example, flexible types of care (C3) often initially caused confusion for both staff and patients, but, after full implementation, lead to greater satisfaction as they allow for more need-adapted forms of treatment. The general finding that concrete experience of new treatment structures or processes enhances their evaluations had been described elsewhere (39). Moreover, the association was robust in our study, as demonstrated by the large concordance of significances (quantitative assessments) with levels of saturation (qualitative assessments; see also sections Concordant and Discordant Results and Discussion of Components).…”
Section: Discussionmentioning
confidence: 79%
“…To give a second example, flexible types of care (C3) often initially caused confusion for both staff and patients, but, after full implementation, lead to greater satisfaction as they allow for more need-adapted forms of treatment. The general finding that concrete experience of new treatment structures or processes enhances their evaluations had been described elsewhere (39). Moreover, the association was robust in our study, as demonstrated by the large concordance of significances (quantitative assessments) with levels of saturation (qualitative assessments; see also sections Concordant and Discordant Results and Discussion of Components).…”
Section: Discussionmentioning
confidence: 79%
“…Considerando o cenário de ampla utilização das metodologias de ensino à distância, avaliar se tal postura é seguida por bons resultados quanto ao processo de construção do conhecimento faz-se necessário, uma vez que investimentos em políticas públicas devem ser avaliados para estudo sobre a eficácia dos métodos utilizados (Mota, Costa, Ronzani, Colugnati, & Rush, 2014). Rush (2003) propõe componentes que devem ser analisados em um processo de avaliação de programas na área de álcool e outras drogas. Dentre estes componentes estão: avaliação de necessidades, planejamento da avaliação, avaliação de processo, avaliação de custos, satisfação de usuários, avaliação de resultados e avaliação econômica.…”
Section: Discussionunclassified
“…Given so many options for designing and implementing more integrated, collaborative systems of substance use services, and with so many potential outcomes to aim for, planners, administrators and evalua- (Rush & Ogborne, 1991;Julian, 1997;Rush, 2004).…”
Section: Planning the Evaluation Of Collaboration And Integration Intmentioning
confidence: 99%